The Use of Notion Application Media in Improving Student Learning Outcomes in PAI Subjects and Class XI Ethics at SMK Negeri 1 Tutar, Polewali Mandar Regency - Muhammad Syahrin (Al-Iftah: Journal of Islamic studies and society, 2023)
This article discusses the use of the Notion application media in improving student learning outcomes in the subjects of Islamic Religious Education and Ethics class XI SMK Negeri 1 Tutar. This study aims to determine whether the use of Notion application media can improve student learning outcomes in the subjects of Islamic Religious Education and Ethics class XI at SMK Negeri 1 Tutar, Polewali Mandar District. The research used is Classroom Action Research (PTK) or Classroom Action Research, which is a research model from Kurt Lewin, which is in the form of a spiral from the first cycle to the next cycle. Each cycle includes planning, acting, observing, and reflecting. The flow is: (1) problem identification, where the researcher determines the problem to be studied; (2) Planning, namely researchers prepare action plans / solutions to solve problems; (3) Implementation, namely researchers carry out actions that have been formulated in the RPP; (4) Observation, namely researchers observe the behavior of students in participating in learning activities; (5) Reflection, in which the researcher records the results of observations and evaluates the results of observations. Based on the results of this research, it is expected for teachers to be more creative in developing learning media, especially the development of notification application media.